The use of proteasome inhibitors in anti-cancer therapy - Marzena Teresa Baran; Paulina Miziak; Katarzyna Bonio (Kazimierz Wielki University, 2020)
Proteins are the basic building blocks of the human body. Most proteins, after fulfilling their function, are degraded with the help of a multi-catalytic proteolytic complex - the 26S proteasome, thanks to its prior labeling with a poly-ubiquitin chain. The ubiquitin-proteasome complex is involved in the control of many important cellular processes. It is involved in the cell cycle, cell proliferation and growth, apoptosis, control of receptor function, quality of proteins in the endoplasmic reticulum, immune response, stress response and other extracellular factors. The dysfunction of the ubiquitin-proteasome pathway plays an important role in the development of many neurodegenerative and neoplastic diseases, as well as diseases with an immune and infectious origin. Accordingly, research is being conducted where the UPS complex is the target of therapeutic activities. Specific proteasome inhibitors are used in cancer therapy. The first to be approved by the FDA was bortezomib, which is a peptide derivative of boric acid. It has the ability to initiate the process of apoptosis by inhibiting the activity of the NF-κB protein, which is a transcription factor. This compound is used in the treatment of multiple myeloma and malignant lung and breast cancers. There are also studies on the combination of proteasome inhibitors with other chemotherapeuticam. There is still growing interest in research aimed at obtaining substances that allowed to control the mechanisms of proteolytic degradation.